Medullary colonic carcinoma with microsatellite instability has lower survival compared with conventional colonic adenocarcinoma with microsatellite instability - Gómez-Álvarez, Miguel A.; Lino-Silva, Leonardo S.; Salcedo-Hernández, Rosa A.; Padilla-Rosciano, Alejandro; Ruiz-García, Erika B.; López-Basave, Horacio N.; Calderillo-Ruiz, German; Aguilar-Romero, José M.; Domínguez-Rodríguez, Jorge A.; Herrera-Gómez, Ángel; Meneses-García, Abelardo (Gastroenterology Review/Przegląd Gastroenterologiczny, 2017)
Introduction: Colorectal medullary carcinoma (MC) is a rare subtype of poorly differentiated adenocarcinoma (PDA) with unclear prognostic significance. Microsatellite instable (MSI) colorectal carcinomas have demonstrated better prognosis in clinical stage II. Aim: To analyze the survival and clinicopathological characteristics of MCs versus PDAs with MSI in clinical stage III. Material and methods: We studied 22 cases of PDAs with MSI versus 10 MCs. Results : Of the 10 MCs, 7 patients were men; the mean age was 57.8 ±5.6 years. The mean tumor size was 9.6 ±4.1 cm, and the primary site was the right colon in 9; 7 patients showed lymph node metastases (LNM) and lymphovascular invasion (LVI). Of the 22 PDA cases, 12 (54.5%) were women with a mean age of 75 ±16.1 years. The mean tumor size was 6.4 ±3.2 cm. Twelve (54.5%) presented in the right colon, 21 (95.5%) showed LNM and 7 (31.8%) LVI. Follow-up was 32 ±8 months, with a 5-year overall survival of 42.9% for MCs and 76.6% for PDAs (p = 0.048). Univariate analysis found local recurrence (p = 0.001) and medullary subtype (p = 0.043) associated with lower survival. Conclusions : Medullary carcinomas were of greater tumor size and associated with more LVI and worse survival versus PDAs with MSI in stage III.